Analisis Hubungan Pengetahuan Wanita Usia 30 – 50 Tahun tentang Inspeksi Visual Asam Asetat dengan Minat dalam Melakukan Pemeriksaan IVA: Analysis of the Relationship between Knowledge of Women Age 30 – 50 Years on Visual Inspection of Acetic Acid with Interest in Performing VIA Examination - Rena Oki Alestari; Angga Arsesiana; Meyska Widyandini (Jurnal Surya Medika (JSM), 2022)
Background: Cervix cancer desease is women's number one killer. Generally, almost all types of cervix cancer diseases are difficult to detect at the early stage. The Purpose of the Study: To analyze the relation between 30 – 50 years old women's knowledge of IVA and their interest in IVA examination. Methods: The research design in this research on cervix cancer is cross-sectional. The sampling technique which was used was simple random sampling. The taking of data was using a close questionnaire. There were 78 respondents of 20-30 years old women in their fertile period randomly selected in the Prenggan district. This study used the skill assessment form of SADARI, modules, and leaflets. The data was analyzed using the correlation test spearman rho. Results: Based on the research, we can conclude that there was a relationship between the knowledge and interest in doing the IVA examination with a correlation coefficient of 0,369 with a significance level of 0,05. Conclusions: Based on the research, we can conclude that there was a relationship between knowledge and interest in doing IVA examination is a low degree of relationship.